Passivating 100 Facets of PbS Colloidal Quantum Dots via Perovskite Bridges for Sensitive and Stable Infrared Photodiodes. (19th October 2022) - Chen, Duo; Liu, Yuxuan; Xia, Bing; Chen, Long; Yang, Yang; Yang, Gaoyuan; Liu, Jing; Lu, Shuaicheng; Ge, Ciyu; Liu, Peilin; Yang, Junrui; Liang, Guijie; et al.
Abstract: Solution‐processed PbS colloidal quantum dots (CQDs) are promising optoelectronic materials for next‐generation infrared imagers due to their monolithic integratability with silicon readout circuit and tunable bandgap controlled by CQDs size. However, large‐size PbS CQDs (diameter >4 nm) for longer shortwave‐infrared photodetection consist mainly of 100 facets with incomplete surface passivation and unsatisfied stability. Here, it is reported that perovskite‐bridged PbS CQDs, in which the 100 facets of the CQDs are epitaxially bridged with CsPbI3– x Br x perovskite, can achieve improved passivation and enhanced stability in comparison with the traditional strategies. The resultant infrared CQDs photodiodes exhibit significantly reduced dark current, nearly 50% enhanced photoresponse, and improved work stability. These superior properties synergistically produce the most balanced performance (with a high −3 dB bandwidth of 42 kHz and an impressive specific detectivity of 6.2 × 10 12 Jones) among the reported CQDs photodetectors. Abstract : This study presents a strategy of halide perovskite bridges for large‐size colloidal quantum dots (CQDs) passivation, where the perovskite heteroepitaxially passivates (100) facets of adjacent CQDs like a bridge. The perovskite‐bridged CQDs photodiodes show the most balanced performance as a high −3dB bandwidth of 42 kHz and an impressive specific detectivity of 6.2 × 10 12 Jones.